ANALYSING ESP LEARNERS’ NEEDS AT UNIVERSITY OF MUHAMMADIYAH MALANG FOR A QUALITY ESP BOOK - Alimin Adi Waloyo (Universitas Islam Negeri Mataram, Indonesia, 2019)
English skills will automatically leave English for Specific Purposes (ESP) students (mechanical enginering, accounting, animal husbandry etc.) more opportunities to access international journals and textbooks related to their study. Therefore this research was conducted in order to analyze (1) learners/ target needs (necessities, lacks and wants) in ESP learning process in class. The learning outcomes were then used to determine ESP learning emphasized learners needs. So, the learning activities will be more fun and engaging. The instrument to collect the data was questionnaire (likert scale) distributed to the 64 mechanical engineering students of University of Muhammadiyah Malang (UMM) as the subject. The data was analyzed using a simple statistical measurement for interpretation purposes. The research finding was divided into three. Firstly, the students necessities for ESP learning were to get connected globally through English and to prepare them for higher education. Secondly, their lacks of English competence are that they have less sufficient perfomance to complete the exercises in class. Lastly, regarding their wants, they expected that English would pave a road to gain a decent job in an international company.Therefore, ESP development has to focus on the students’ preferences above as the priority. It means that ESP English teaching and textbooks ones are suggested to pay attention to those findings.